COMPARISON OF THE HAWALAH SYSTEM IN THE FIQH MUAMALAH AGAINST THE TURKEY’S MAJALLAH AL-AHKAM AND THE INDONESIAN CIVIL LAW - -, Fahriansah (IAIN Langsa, 2020)
This paper examines the system of debt transfer (hawalah) contained in the fiqh muamalah, then it is calculated against the hawalah system in the Majallah al-Ahkam al-Adliyah and the Civil Law of Indonesia. Because there are some differences between the three systems. This paper is conducted through a research study of litaration. The result of this study, if the system is in fiqh compared to the hawalah system contained in the Majallah Al-Ahkam Al-Adliyah, the author only found a slight change. However, when compared with Indonesian Civil Law, there are many changes ranging from the underwriting, the agreement, and the parties involved in the hawalah process.